La chanson, une technologie du genre: Éric Lapointe et l'exaltation d'une virilité rebelle - Boisclair, Isabelle (Quebec Studies, 2008)
Keywords: approches et analyses; arts; culture populaire; discipline; genre; hétérosexisme; masculinité; ressource en ligne; systèmes d'oppressions; études littéraires

All these poses, such beautiful poses: Articulations of queer masculinity in the music of Rufus Wainwright - Jones, Matthew J. (Université de Géorgie, 2008)
Singer-composer Rufus Wainwright uses specific musical gestures to reference historical archetypes of urban, gay masculinity on his 2002 album Poses. The cumulative result of his penchant for pastiche, eschewal of traditional musical boundaries, and self-described hedonism, Poses represents Wainwright's direct engagement with the politics of identity and challenges dominant constructions of (homo)sexuality and masculinity in popular music. Drawing from a vast lexicon of musical styles, he assembles an idiosyncratic persona, ignoring several decades of pop with an "utter lack of machismo [and] a freedom that comes to outsiders disinterested in meeting the requirements of the dreary status quo." Though analysis of musical and lyrical characteristics of Poses, I establish a dialectic between Wainwright's musical persona and four historical modes of urban gay masculinity: the 19th Century English Dandy, the French flaneur, the 20th Century gay bohemian, and the "Clone." In doing so, I introduce Wainwright as a reinvigorating force, resuscitating the subversive potential of radical gay sexuality as a 21st Century model for imagining gay male subjectivity.
Keywords: 2000 à aujourd'hui; 2000-2009; DIG; approches et analyses; arts; culture populaire; discipline; discours dominant; ethnographie; genre; hétérosexisme; masculinité; musique; mémoires/thèses; périodes historiques; queer; ressource en ligne; systèmes d'oppressions

Masculinités variables en temps de crise : deux auteurs-compositeurs-interprètes : fixer le temps, de Dumas. Tacca / La Tribu, 2006 ; Les vendredis, de Stefie Shock. Atlantis, 2006 - Boisclair, Isabelle (Spirale, 2007)
Keywords: 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; arts; culture populaire; discipline; genre; hétérosexisme; masculinité; périodes historiques; québec; ressource en ligne; régions géographiques; systèmes d'oppressions; études littéraires

Lesbian inscriptions in francophone society and culture - Günther, Renate; Michallat, Wendy (Durham Modern Languages, 2007)
This book represents the first comprehensive collection of essays in English dedicated entirely to the study of lesbian inscriptions in francophone society and culture. Spanning the period from the early nineteenth to the twenty-first century, the volume offers a range of interdisciplinary perspectives on ways in which lesbianism has been represented and represented itself, with essays on poetry and the novel, contemporary film and television, photography and architecture. These essays will appeal to students and scholars of gender studies and French literature and culture.
Keywords: afrique; amériques; approches et analyses; arts; belgique; canada; discipline; europe; france; hétérosexisme; identités LGBTQIA2+; régions géographiques; systèmes d'oppressions; études littéraires

King King théorie - Despentes, Virginie (Grasset, 2006)
J'écris de chez les moches, pour les moches, les frigides, les mal baisées, les imbaisables, toutes les exclues du grand marché à la bonne meuf, aussi bien que pour les hommes qui n'ont pas envie d'être protecteurs, ceux qui voudraient l'être mais ne savent pas s'y prendre, ceux qui ne sont pas ambitieux, ni compétitifs, ni bien membrés. Parce que l'idéal de la femme blanche séduisante qu'on nous brandit tout le temps sous le nez, je crois bien qu'il n'existe pas. V.D.
Keywords: 2000 à aujourd'hui; 2000-2009; anticapitalisme; approches et analyses; cours; cycles supérieurs; discipline; discours dominant; europe; fem1000; fem7000; france; hétérosexisme; identités LGBTQIA2+; lit3220; littérature; premier cycle; périodes historiques; régions géographiques; sexualité; systèmes d'oppressions; thématiques; travail; travail du sexe; violences; violences sexistes et sexuelles; études littéraires

La pornographie comme espace de décentrement du discours hétéronormatif : l'exemple du roman Baise-moi de Virginie Despentes - Ouellette, Julie (Université du Québec à Montréal, 2005)
Keywords: 2000 à aujourd'hui; 2000-2009; IREF; approches et analyses; arts; discipline; europe; france; hétérosexisme; identités LGBTQIA2+; mémoires/thèses; périodes historiques; queer; régions géographiques; systèmes d'oppressions; thématiques; études littéraires

Queering the Crip or Cripping the Queer?: Intersections of Queer and Crip Identities in Solo Autobiographical Performance - Sandahl, Carrie (GLQ: A Journal of Lesbian and Gay Studies, 2003)
As the interdisciplinary field of disability studies develops its own theoretical paradigms, it necessarily borrows from various sources. Such borrowing means that disability scholars have not had to reinvent the wheel but have been able to build on the conceptual foundations of identity-based theories that have grown out of other interdisciplinary fields, such as gender studies and critical race studies. But disability studies offers as much to its predecessors as it borrows from them. This essay explores the productive reciprocity between queer theory and disability studies, queer identity and crip identity, queer activism and crip activism.
Keywords: EDI; LGBTQIA2+; approches et analyses; arts; capacitisme; care; corps; cours; crip; discipline; hétérosexisme; identités LGBTQIA2+; intersectionnalité; lit4700; militance; premier cycle; queer; ressource en ligne; santé; systèmes d'oppressions; thématiques; théâtre; études littéraires

Parce que les lesbiennes ne sont pas des femmes : autour de l'oeuvre politique, théorique et littéraire de Monique Wittig - Bourcier, Marie-Hélène; Robichon, Suzette (Éditions Gaies et Lesbiennes, 2002)
Avec Les Guérillères et Le Corps lesbien, l'œuvre littéraire de Monique Wittig a irradié le mouvement féministe et lesbien en train de naître. En 1978 et 1979, deux nouveaux textes théoriques de Monique Wittig faisaient sensation : " On ne naît pas femme " et " La Pensée straight " qui se conclut par ces mots : " Il serait impropre de dire que les lesbiennes vivent, s'associent, font l'amour avec des femmes car la femme n'a de sens que dans les systèmes de pensée et les systèmes économiques hétérosexuels. Les lesbiennes ne sont pas des femmes. " Pour la première fois, un point de vue lesbien politique était affirmé à haute voix sans circonlocution ni métaphore. Au delà même de la scission politique et théorique qu'elle entraîna, cette simple phrase " les lesbiennes ne sont pas des femmes " eut un effet catalyseur. La force du colloque de juin 2001 est d'avoir su insérer ces réflexions et analyses littéraires dans des perspectives qui concernent l'histoire contemporaine des lesbiennes, leurs mouvements politiques, les enjeux et les polémiques qui les intéressent.
Keywords: approches et analyses; arts; discipline; europe; france; hétérosexisme; lesbianisme; personnes lesbiennes; régions géographiques; systèmes d'oppressions; études littéraires

Femme/Butch family romances - Harris, Laura A. (Journal of Lesbian Studies, 2002)
My essay theorizes femme/butch family romances against the grain of dominant feminist and lesbian thought that desexualizes the space of mother/daughter desire. I do so through a reading/recoding of the infringing incestuous mommie-boy desires that surface in an archetypal lesbian novel, Jane Rule's Desert of the Heart.
Keywords: approches et analyses; arts; butch; discipline; genre; hétérosexisme; personnes lesbiennes; queer; ressource en ligne; systèmes d'oppressions; études littéraires